Phytoremediation of Eel (Anguilla bicolor bicolor) rearing wastewater using amazon sword (Echinodorus amazonicus ) and water jasmine (Echinodorus palaefolius) - Hany Handajani; Widanarni Widanarni; Tatag Budiardi; Mia Setiawati; Sujono Sujono (Journal Omni-Akuatika)
Management of aquaculture wastewater is still the major problems in fisheries, especially in intensive systems. Intensively aquaculture activities often increase organic matter and nutrients (N and P) in the water.  The study was conducted to evaluate the phytoremediator performance of Echinodorus amazonicus and Echinodorus palaefolius in removing inorganic nitrogen and orthophosphate from aquaculture wastewater with the recirculation system. This study used a completely randomized design with three treatments and 3 replications. The treatments of this study were P1: E. amazonicus,  P2: E. palaefolius and P3: control (without aquatic plants). The tested fish were elvers  which average weight 6.98 ± 0.19 g,  and  fish density was 4 gL-1. Elvers reared in an aquarium that containing 48 L in  a recirculation system. The paste feed which protein level of  45.25% was given at satiation 3 times/day. Elvers reared for 60 days. The results showed that E. palaefolius significantly reduced concentrations of total ammonia nitrogen (TAN), nitrite (NO2), nitrate (NO3) and orthophosphate (PO4) with an efficiency of 27.10 ± 2.42%; 45.03 ± 9.77%; 20.94 ± 1.29% and 14.19 ± 3.05%, respectively higher than E. amazonicus and control. The best result of elver’s performance (SGR and FCR) was in treatment P2 (E. palaefolius), i.e.  1.19 ± 0.18% and 1.57 ± 0.30. Based on the results of this study, it can be concluded that the use of E. palaefolius as phytoremediator in eel culture with recirculation system can removed inorganic nitrogen and orthophosphate more optimal compared to other treatment.